1999
DOI: 10.1007/bf03343656
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and regulation of variant thyroid hormone receptor isoforms in developing rat testis

Abstract: High affinity-low capacity nuclear triiodothyronine (T3) receptors (TRs), identified as a product of c-erbAalpha proto-oncogene, are expressed in prepubertal rat Sertoli cell. At this age, exogenous T3 treatment as well as hypothyroidism affects Sertoli cell functions. We examined the ontogenetic expression pattern of TRs in the rat testis. Northern analysis confirms that TRs are expressed at high level from fetal development until prepubertal period. RNase protection analysis demonstrates that TRalpha2, the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Sertoli cell function has received much attention since the finding of functional T 3 receptor expression in prepubertal testes. An ontogenetic pattern of TRa 1 and TRa 2 expression and of b mRNA receptor has been demonstrated in Sertoli cells (78,79). This allows the use of the testis as a naturally occurring model for studying the role of TR in the modulation of gene expression and cellular function in vivo (73,79).…”
Section: Tri-iodo-l-thyroninementioning
confidence: 94%
“…Sertoli cell function has received much attention since the finding of functional T 3 receptor expression in prepubertal testes. An ontogenetic pattern of TRa 1 and TRa 2 expression and of b mRNA receptor has been demonstrated in Sertoli cells (78,79). This allows the use of the testis as a naturally occurring model for studying the role of TR in the modulation of gene expression and cellular function in vivo (73,79).…”
Section: Tri-iodo-l-thyroninementioning
confidence: 94%
“…Palmero et al [80] and Jannini et al [46] demonstrated high-affinity and low-capacity TR in fetal, neonatal, and prepubertal rat Sertoli cells. These authors showed that the presence of TR in the testis is very high in fetal and neonatal rats and that TR levels decrease in prepubertal rats to eventually become undetectable in adult animals [44][45][46][47]. They also suggest that Sertoli cells are the only testicular cells that contain TR, suggesting that they are the only targets for T3 action in the testis.…”
Section: T3 Receptors In Testicular Cellsmentioning
confidence: 97%
“…Jannini et al [44,45,47] claimed that age-dependent expression of TRa1, TRa2, and TRa3 is present in the testis, whereas TRb is completely absent in both human and rat testis. Some immunohistochemical and mRNA expression studies claim otherwise; they found that rat and pig testis contain TRb [21,33,56,77,87,93,94].…”
Section: T3 Receptors In Testicular Cellsmentioning
confidence: 99%
“…TH receptors are highly expressed in neonatal Sertoli cells, indicating that the developing Sertoli cells and testis may be important TH targets (Jannini et al 1999, Rao et al 2003. In this context, Jannini et al (1995) and provided strong evidence that THs regulate Sertoli cell proliferation and differentiation in the neonatal testis.…”
Section: Introductionmentioning
confidence: 99%